Measurement Matters: Offense Types and Specialization - Humphrey, Tamara (Journal of interpersonal violence, 2021)
Offender specialization—the tendency to repeat specific offenses—is the basis of practical orientations toward managing offending by the criminal justice system. Alternatively, dominant criminological paradigms postulate that offending versatility is the norm. We consider this incongruity by, first, considering “practice” in action, through the examination of the designations used by the Canadian criminal justice system to categorize offenders based on the assumption of specialization, and whether these determinations accurately reflect the offending behavior of offenders who have committed violent interpersonal crimes. Second, we compare several other measures of specialization among our population to investigate whether different measures produce similar findings regarding the repeat of specific offense types. Official criminal record data, from first offense to the end of the study date (2014), for a population of offenders in a western Canadian city who were convicted of violent interpersonal sexual and nonsexual offenses (N = 110), were used to examine the tendency toward specialization. We employ three measures of specialization: the specialization threshold, mean percent specialization, and the diversity index—across this group of career criminals. Results indicate that evidence of specialization depends on the way in which it is measured. Although there is some support for the treatment of individuals who sexually offend against children as a distinct group compared with those who are violent (sexually or nonsexually) toward adults, there is greater evidence of versatility among all offenders than there is of specialization. Our findings suggest that establishing the risk of future offending using models other than those geared toward offense specialization may be more effective for addressing offending patterns.